THE FUTURE OF TOURISM IN THE DIGITAL AGE - Zokirova , Parvina (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
In recent decades, technology has developed rapidly, transforming almost every aspect of our lives. Tourism is no exception. Smartphones, virtual and mixed reality, augmented reality, as well as digital platforms and online services are fundamentally changing the way we travel. The digital age is reshaping the questions of what the tourist experience should be like, to whom and what services should be offered, and what travelers should expect. This article provides a comprehensive analysis of the impact of virtual, mixed and augmented reality technologies on the tourist experience, the role of digital platforms, the opportunities and potential risks, and future trends.